A Design Model of Special Vocational High School for Children with Visual Impairment - Maknun, Johar; Barliana, M Syaom; Cahyani, Diah (Indonesian Journal of Science and Technology, 2019)
This paper aimed to describe architectural design model of vocational high school that is accessible and meets the behavioral needs of children with visual impairment. The method used was a rational design method or often called as a glass box method, which was divided into four steps: 1) design criteria; 2) children with visual impairment’s behaviour; 3) programming; 4) designing model. The design criteria was combined based on its accessibility, space, sensory awareness, enhancement of learning, flexibility and ability, health and well-being condition, safety and security, sustainability, incorporation of nature environment and buildings, and availability of open space. These principle implemented from outside to inside the building, as well as from the site, landscape, building to interior of classroom. We believe that this study gives important for the need of architectural building model for students with special needs.